AI in tertiary education: progress on research and practice - Thompson, Kate; Corrin, Linda; Lodge, Jason M. (Australasian Journal of Educational Technology, 2023)
Generative artificial intelligence (AI) has had a significant impact in tertiary education for practitioners and researchers during 2023. We review the way in which academics have made sense of generative AI, revisit our proposed research agenda and reflect on our changing roles as academics in relation to learning, teaching, design and policy.